Inheritance Transitioning to Gift in The Issuance of Land Certificates: an Islamic Legal Perspective - Nur Afni A.; Sarah Suleman; Arfan Arfan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
In Islamic law, inheritance and gifts are two distinct concepts with different rules and implications. However, in practice, there is often confusion between these two, particularly in the context of land ownership and certification. This confusion can lead to legal complications and potential disputes. This research aims to elucidate inheritance and gifts in Islam and the factors causing and legal position of the transition of inheritance status to gift status in the issuance of land certificates. This study employs a qualitative descriptive research approach focused on textual analysis, utilizing normative juridical and conceptual approaches. The findings are as follows: Firstly, the factors leading to the transition of inherited land status to gifted land include the community’s lack of understanding regarding the difference between inheritance and gifts, the absence or loss of supporting documents, and the facilitation of land registration. Secondly, the legal position of changing the status of inherited land to gifted land in the issuance of land certificates arises due to the loss of supporting documents and to prevent future complications. This action is permitted based on considerations of maṣlaḥah (public interest) to safeguard property and prevent harm. It also falls under emergency conditions where the fiqh principle states that every necessity justifies what is forbidden, but only for administrative purposes. The land remains inherited land in accordance with the fiqh principle that the intention and substance, not the expressions and formalities, are the reference points in transactions.